Spotify as a Tool for Pronunciation Enhancement Among Eighth Graders: A Quasi-Experimental Study - Sellinda Putri; Hastini; Usman, Sriati; Bochari, Siska (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to find out the effect of the using Spotify application, using English songs and podcasts, affects students' pronunciation at SMP Negeri Model Terpadu Madani Palu. The research used a quasi-experimental design with two groups: an experimental class that used Spotify and a control class that used traditional methods. The sample consisted of two eighth-grade classes chosen using purposive sampling. Data was collected through pre-tests and post-tests to measure students' pronunciation before and after the treatment. The results showed that the average score of the experimental class improved significantly from 14.58 to 24.77, while the control class increased from 20.83 to 38.89. The Wilcoxon Signed Ranks test confirmed that the experimental class had a significant improvement (Z = -3.963, p = 0.000). However, the Mann-Whitney test showed no significant difference between the experimental and control classes (p = 0.677). This means that while Spotify helped improve students’ pronunciation, it was not proven to be more effective than traditional teaching methods. In conclusion, using the Spotify application can help students improve their pronunciation, especially for the consonant sounds /ʃ/, /ʒ/, /θ/, and /ð/. Even though the improvement was not greater than the conventional method, Spotify still made learning more interesting and interactive for students.